LE CANCER DU SEIN A PRÉDISPOSITION GÉNÉTIQUE ÉTUDE DE LA MUTATION BRCA1 - KRADIA, ilhem; BOUKSIBA, malika (My University, 2017)
Despite advances in treatment and the emergence of targeted therapies, breast cancer remains the leading cause of cancer death in women. It remains an ill-known disease with unpredictable evolution and current clinical and histological classifications do not allow to fully predict the prognostic and predictive parameters of response to treatments. The heterogeneity of mammary cancer is found at the histological, phenotypic and molecular levels. Current clinical and histological classifications do not allow for a complete prediction of prognostic and predictive parameters. The predisposition to breast cancer is inherited as a dominant trait. The presence of mutations with founding effect in the founding populations facilitates the discovery of highly penetrating alleles in high-risk individuals within families with an inherited susceptibility to breast cancer. Our goal is to do a bibliographies study on the mammary gland and the importance of the BRCA1 mutation in breast cancer.
Keywords: Glande Mammaire; Cancer du Sein; Mutation BRCA1; Breast Gland; Breast Cancer; BRCA1 mutation.